Catatonia in a 13-Year-Old With T-Cell Lymphoblastic Lymphoma Following Intrathecal Methotrexate - Raquel Lazarowitz; Jennifer Picado; Jitka Stankova (Journal of Pediatric Hematology/Oncology, 2026)
Background: Methotrexate neurotoxicity is a recognized complication in pediatric lymphoid malignancies, presenting with seizures, stroke-like episodes, or leukoencephalopathy. Catatonia is a rare and underrecognized manifestation. Observation: A 13-year-old girl with T-cell lymphoblastic lymphoma developed agitation, confusion, and catatonia 5 days after intrathecal methotrexate. Investigations excluded structural, infectious, metabolic, and malignant causes. Psychiatry confirmed catatonia (Bush-Francis Catatonia Rating Scale 21-22). Lorazepam led to rapid improvement. Intrathecal methotrexate was later reintroduced with leucovorin rescue without recurrence. Conclusions: Catatonia may represent an uncommon presentation of methotrexate neurotoxicity. Early recognition and lorazepam treatment are critical, and cautious methotrexate rechallenge may be feasible.